A study on the feasibility of wrist pulse determination using electrical impedance measurement. (19th March 2012) - Cevei, Patricia-Lidia; Cevei, Mariana-Lidia
The results presented in the present paper are concentrated on the determination of pulse using electrical impedance method at the wrist level. The electric field distribution in an arm segment was estimated by simulation of the electric field changes due to conductivity modifications determined by pulse. It was found that the motion induced conductivity changes, due to arm geometry deformation, are similar in magnitude with the blood related changes. The simulation data was validated in an experiment using a simple test circuit. The data ranges of pulse induced changes of conductivity prove the feasibility of the application of the method in practice. Additional work is necessary to device a method to eliminate motion artefacts by appropriate digital signal processing.